As Y and x are related with each other therefore, whenever, there will be a change in the value of x, there will be an obvious change in y. Now, as there is 2% change in x therefore, the new value will be x + 0.2x = 1.2x. Now putting this new value in the equation we will get,

y = x

y = (x + 0.2x)

y = (1.2x)

y = 1.728x

Now, change in y = 1.728x

Percentage change in y = (0.728x

Percentage change in y = (0.728x

Percentage change in y = 72.8x

y = x

^{3}y = (x + 0.2x)

^{3}y = (1.2x)

^{3}y = 1.728x

^{3}Now, change in y = 1.728x

^{3}- x^{3 }Change in y = 0.728x^{3}Percentage change in y = (0.728x

^{3}/x^{3})*100Percentage change in y = (0.728x

^{3}/x^{3})*100Percentage change in y = 72.8x

^{3}%